ANALISIS PROSES KERJA PENGELUARAN SPARE PART INDUSTRI MANUFAKTUR - yevita nursyanti; Siti Dhetia (Jurnal Manajemen, 2021)
This research aims to analyze the work procedures contained in the activity of spare part issuance and provide suggestions for improvement for the work procedures for spare part storage. The data used is the Standard Operating Procedure (SOP) for spare part expenditure as well as existing problems. The problem that occurs is that the storage work process in the spare part warehouse does not yet have a Standard Operating Procedure (SOP) and the work process for the removal of spare parts is not carried out in accordance with existing procedures. That caused a difference in the actual amount of stock with the system. The problem in the storage process is that spare parts are not stored in accordance with the storage location and for the warehouse worker expenditure process does not use the Proof of Request for Goods (BPB) or related documents. The cause of the problem was analyzed using the fishbone diagram method with several factors, namely human, method, environment, machine and material factors and used a questionnaire to determine the potential root causes of the problem. For proposed improvements using the 5W + 1H method. Based on the results of the analysis of the 5W + 1H method, the proposed improvement is in the form of a Standard Operating Procedure (SOP) for storing spare parts and making the identity of each spare part that is stored.